Social Responsibility in Advancing the Role of Universities in Sustainable Economic Development in Iraq - Mahmood, Prof. Dr. Dhuha Adil Mahmood Al-Ani (Sulaimani Journal for Humanities, 2026)
Universities, represented by their technical colleges, work to provide society with trained personnel to use modern machines that rely directly on modern technology. This makes these users supporters of local industries, which in turn increases national income, raises citizens' well-being, and ensures a longer-term sustainability of human and material resources. Universities play a major role in developing the local community by directing their activities toward all members of society and its institutions with the goal of improving social, economic, and cultural living conditions. The mission of university education is to create minds that produce and innovate in all fields. (Amer, 2007: 37-53), Malaysia is poised to become one of the developed nations, transitioning from a developing country to a second-world country by the year 2030, following the reform of the admissions plan for colleges and institutes affiliated with universities. In such countries, higher education and vocational training are regarded as fundamental and integral components of life, serving as primary tools for improving the standard of living and advancing societal well-being. In anticipating the future dimensions of education in the 21st century, "learning for work" has emerged as one of the core pillars of education. It plays a critical role in training and preparing individuals for professional life by equipping them with practical skills and connecting theoretical knowledge with real-world application — in alignment with the evolving demands of the labor market. In production and service sectors, particularly in developed countries, it is now assumed that graduates who are employable and capable of integration into the workforce can contribute to enhancing institutional competitiveness. They do so by fostering innovation and creativity, increasing productivity, and improving output — all of which depend heavily on the acquisition and effective application of knowledge. This research adopted a descriptive methodology and aimed to achieve the following objectives: 1. To explore the role of small and medium-sized enterprises (SMEs) in sustainable economic development. 2. To examine China as a model for sustainable economic growth. 3. To assess the current state of small economic projects in Iraq.
Keywords: Social Responsibility; Universities; Economic Development; Sustainable